1995
DOI: 10.1007/bf02935686
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of GH receptor and GH binding protein during pregnancy in the GH deficient rat

Abstract: During pregnancy there are dramatic changes in the endocrine and metabolic status of the mother: growth hormone (GH) is an important regulator of growth and development. A proportion of GH is bound by specific GH binding proteins (GHBP) that closely resemble the GH receptor (GHR). In the rodent both GHBP and the GHR are considered to be GH dependent, and consequently during pregnancy the increase in serum GH is associated with an increase in GHBP. To examine whether an increase in maternal GH is obligatory for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The GHBP levels reported in this study were rather low for pregnant rats, as circulating GHBP levels normally increase during pregnancy (Barnard & Waters 1997). A 5-fold increase in GHBP levels has previously been observed in pregnant rats compared with non-pregnant rats (R Barnard, S M Woodall & B H Breier, unpublished observations), which was similar to that reported in the dwarf rat (Gargosky et al 1995). Plasma GHBP levels in the saline-treated undernourished dams were similar to those measured in the saline-treated ad libitum fed rats.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The GHBP levels reported in this study were rather low for pregnant rats, as circulating GHBP levels normally increase during pregnancy (Barnard & Waters 1997). A 5-fold increase in GHBP levels has previously been observed in pregnant rats compared with non-pregnant rats (R Barnard, S M Woodall & B H Breier, unpublished observations), which was similar to that reported in the dwarf rat (Gargosky et al 1995). Plasma GHBP levels in the saline-treated undernourished dams were similar to those measured in the saline-treated ad libitum fed rats.…”
Section: Discussionsupporting
confidence: 89%
“…Plasma GHBP levels in the saline-treated undernourished dams were similar to those measured in the saline-treated ad libitum fed rats. Similar serum GHBP levels were observed in pregnant dwarf rats with an isolated GH deficiency (Gargosky et al 1995). The effect on GHBP concentrations following GH and IGF-I treatment to pregnant rats has not been reported to date, but in male rats other studies have reported conflicting effects of hormone treatment on circulating GHBP levels.…”
Section: Discussionsupporting
confidence: 60%
“…This may also be regulated by GH itself because continuous exposure to elevated GH in nonpregnant rats results in the up-regulation of GHBP (9,34). In contrast, however, it is interesting to note that a pregnancy-associated rise in GHBP is not driven by GH (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although existing dwarf strains are useful in studies of GH or IGF-1 action (Skottner et al, 1989;Gargosky et al, 1995), neither show significant growth responses to GH secretagogues. Although existing dwarf strains are useful in studies of GH or IGF-1 action (Skottner et al, 1989;Gargosky et al, 1995), neither show significant growth responses to GH secretagogues.…”
Section: Discussionmentioning
confidence: 99%